2016
DOI: 10.1016/j.colsurfb.2016.04.043
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chirality on catalytic generation of nitric oxide and platelet behavior on selenocystine immobilized TiO2 films

Abstract: As nitric oxide (NO) plays vital roles in the cardiovascular system, incorporating this molecule into cardiovascular stents is considered as an effective method. In the present study, selenocystine with different chirality (i.e., l- and d-selenocystine) was used as the catalytic molecule immobilized on TiO2 films for decomposing endogenous NO donor. The influences of surface chirality on NO release and platelet behavior were evaluated. Results show that although the amount of immobilized l-selenocystine on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…The results proved that the hydrophilic TiO 2 could significantly decrease Fib denaturation. Fan et al [ 61 ] used quartz crystal microbalance to determine the adsorption of bovine serum albumin (BSA) and Fib on the L- and D-selenocystine (L-Se/D-Se) immobilized TiO 2 films, and found that surface chirality led to different steric interactions between the negatively charged L-Se/D-Se surfaces and the negatively charged BSA and Fib, which in turn influenced hydrogen bonding and hydrophobic interaction, and eventually influenced protein adsorption. Svendsen et al [ 62 ] used ellipsometry to study the competitive adsorption of human serum albumin (HSA), human immunoglobulin G (IgG) and laminin-1 on the spin-coated and sintered hydroxyapatite (HA) surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…The results proved that the hydrophilic TiO 2 could significantly decrease Fib denaturation. Fan et al [ 61 ] used quartz crystal microbalance to determine the adsorption of bovine serum albumin (BSA) and Fib on the L- and D-selenocystine (L-Se/D-Se) immobilized TiO 2 films, and found that surface chirality led to different steric interactions between the negatively charged L-Se/D-Se surfaces and the negatively charged BSA and Fib, which in turn influenced hydrogen bonding and hydrophobic interaction, and eventually influenced protein adsorption. Svendsen et al [ 62 ] used ellipsometry to study the competitive adsorption of human serum albumin (HSA), human immunoglobulin G (IgG) and laminin-1 on the spin-coated and sintered hydroxyapatite (HA) surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…However, Cys10 has significantly lower adhered platelets than Cys1. These results can prove that Cys10 has the ability to anti-platelet adhesion and activation [ 21 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 96%
“…Wang et al were the first to report the activity of selenium compounds that decompose GSNO to generate NO in the presence of reducing agent GSH. [93] Based on this knowledge, several organoselenium species, including selenocystamine (SeCA), [94][95][96][97] selenocystine, [98] 3,3diselenodipropionic acid (SeDPA), [99][100][101] and 2,2'-diselenodiethanol (SeDO) [102] were studied by several groups to generate NO from RSNOs. The catalytic mechanisms of Se-contained enzyme mimics to decompose RSNOs to release NO in the presence of GSH are concluded as follows: [99] RSe Se-catalyzed reactions are highly selective towards RSNOs and exhibit no catalytic activity for nitrite or nitrate reduction.…”
Section: Seleniummentioning
confidence: 99%